How could local environmental innovations become a national policy?—A qualitative comparative study on the factors influencing the diffusion of bottom-up environmental policy innovations - Jiliang Zhang; Shuya Xing (PLoS ONE, 2025)
Innovation diffusion in China’s local environmental governance occurs both horizontally and vertically from the bottom up. This process is critical to improving environmental policies and advancing our understanding of how local innovations spread. To explore this phenomenon, the study applies fuzzy-set qualitative comparative analysis (fsQCA) to 17 environmental cases. It examines five key factors: central agenda setting, recognition by central government departments, focal events, policy innovation costs and difficulties, and diffusion among local governments. The findings indicate that national policy integration is driven by five distinct pathways, rather than by any single factor. These pathways fall into three broader models: Central Guidance, Drive by Centre and Society, and Local Autonomy. This study introduces a new analytical framework to explain the vertical diffusion of local environmental innovations within China’s governance structure. It deepens our understanding of innovation diffusion in local governance and provides practical guidance for both central and local governments. Additionally, it lays a foundation for future research on environmental policy diffusion.